Tertiary lymphoid structures, drivers of the anti‐tumor responses in human cancers. Issue 1 (May 2016) - Dieu‐Nosjean, Marie‐Caroline; Giraldo, Nicolas A.; Kaplon, Hélène; Germain, Claire; Fridman, Wolf Herman; Sautès‐Fridman, Catherine
Summary: The characterization of the microenvironment of human tumors led to the description of tertiary lymphoid structures (TLS) characterized by mature dendritic cells in a T‐cell zone adjacent to B‐cell follicle including a germinal center. TLS represent sites of lymphoid neogenesis that develop in most solid cancers. Analysis of the current literature shows that the TLS presence is associated with a favorable clinical outcome for cancer patients, regardless of the approach used to quantify TLS and the stage of the disease. Using several approaches that combine immunohistochemistry, gene expression assays, and flow cytometry on large series of lung tumors, our work demonstrated that TLS are important sites for the initiation and/or maintenance of the local and systemic T‐ and B‐cell responses against tumors. Surrounded by high endothelial venules, they represent a privileged area for the recruitment of lymphocytes into tumors and generation of central‐memory T and B cells that circulate and limit cancer progression. TLS can be considered as a novel biomarker to stratify the overall survival risk of untreated cancer patients and as a marker of efficient immunotherapies. The induction and manipulation of cancer‐associated TLS using drug agonists and/or biotherapies should open new avenues to treat cancer patients.